Use of anatomy for the identification of vegetal drugs from two species of Justicia (Acanthaceae) marketed as “anador” - Aoyama, Elisa Mitsuko; Indriunas, Alexandre (Scientia Plena, 2015)
Various medicinal plants used in Brazil are called by the name “anador”, including Justicia pectoralis Jacq. and J. gendarussa Burm. f. Both plants are used due to the anti-inflammatory and analgesic properties of their components. Their leaves are used, and they can be sold fragmented, making the precise identification difficult. This study aimed to verify the use of leaf epidermal anatomy of the species for the identification of the plant drugs. For the characterization of the epidermis, paradermic sections were obtained from the both sides and for the samples of fragmented leaves, these were dried and later fragmented. The sections and the fragments were clarified and mounted on temporary slides. The main features that allowed anatomical differentiation between the species under study and also the fragmented leaves were the sinuosity of periclinal cell walls, the presence of tector trichomes in J. pectoralis and the absence of stomata on the adaxial side and the presence of abnormal stomata in J. gendarussa. According to the results obtained, it has been found that due to the drying and fragmentation process used, the anatomical structures observed were still present, with anatomical differentiation between species being possible.